Medytacyjny wykład o miłości Bożej w świetle poematu Kaspra Twardowskiego Pochodnia miłości Bożej z piącią strzał ognistych - Kaczor-Scheitler, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
This article presents an analysis of two meditative lectures (poetic songs) about God’s love which appeared in Kasper Twardowski’s poem entitled Pochodnia miłości Bożej z piącią strzał ognistych, the shorter First Song delivered by Mary Mother of God and the longer Fifth Song presented by Mary Magdalene. In both of these poetic lectures, the poet showed the power of God’s love to human beings and man’s pursuit of the mystic union with The Creator. Twardowski’s poem, which was classified as meditative literature, so popular in Baroque, was based on the art of meditation and the ideas of Ignatius of Loyola. The poem is regarded as autobiographical and written with didactic objectives. The author probably thought that his personal internal history deserved propagating and his spiritual conversion will offer readers a specific exemplum which will encourage imitating virtue.